Between Innocence and Experience: How Analysis Might or Might Not Have Affected My Hearing of Milton Babbitt's Music. Issue 2 (4th May 2021) - Mead, Andrew
Abstract : This article discusses aspects of Milton Babbitt's music read from the point of view of a listener's emotional engagement with the music, frequently understood in terms of playfulness.